Progesterone Receptor Agonists and Antagonists as Anticancer Agents - Chakraborty, A.; Chatterjee, S.; Roy, P. (Mini Reviews in Medicinal Chemistry, 2010)
Progesterone is a major female steroid hormone produced by the ovarian corpus luteum and by the placental syncyiotrophoblast during the second trimester. The biological effects of this steroid hormone are mediated by the ubiquitously expressed progesterone receptor. The exact link between progesterone and female reproductive organ cancer is a controversial issue with various cross-talks. The present review summarizes recent trends in the development of some (anti)progestagen in the cure and management of breast and uterine cancers.
Keywords: progestagens